TAKMILAH: MENUJU TEORI SASTRA ISLAMI - Supriadi, Asep (Balai Bahasa Jawa Timur, 2011)
Banyaknya karya sastra Indonesia yang bernuansa islami sejak tahun 2000-an telah dijadikan objek kajian sastra. Pengkajian karya sastra islami tersebut sangat relevan jika menggunakan pendekatan teori sastra Islam. Pendekatan teori sastra Islam yang dianggap sesuai dengan karakter sastra Indonesia bernuansa islami adalah teori sastra Islam Melayu Malaysia. Para pakar sastra Melayu telah berhasil menciptakan teori sastra islami, di antaranya Shafie Abu Bakar yang telah memperkenalkan teori sastra Islam yang disebut dengan teori takmilah. Abstract: The outburst of Indonesian Islamic literatures has been the object of literary study since the 2000s. The study of Islamic literature is very relevant when using the approach of Islamic literary theory. The approach of Islamic literary theory is considered in accordance with Indonesian Islamic literary character. It is descending from the literature of Malay. The Malay literary experts have succeeded in creating an Islamic literary theory. Shafie Abu Bakar has introduced Islamic literary theory called the theory Takmilah. Key Words: Islamic literature, theory of Takmilah